2023
DOI: 10.3390/ijms24108836
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Enteroendocrine Cells: Present and Future Druggable Targets

Abstract: Enteroendocrine cells are specialized secretory lineage cells in the small and large intestines that secrete hormones and peptides in response to luminal contents. The various hormones and peptides can act upon neighboring cells and as part of the endocrine system, circulate systemically via immune cells and the enteric nervous system. Locally, enteroendocrine cells have a major role in gastrointestinal motility, nutrient sensing, and glucose metabolism. Targeting the intestinal enteroendocrine cells or mimick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 142 publications
0
2
0
Order By: Relevance
“…EECs comprise approximately 1% of the intestinal epithelium and secrete hormones and peptides to recruit immune cells [34]. Distinctive staining of CHGA was observed for HROC43, HROC60, HROC159 T2 M4, and HROC239 T0 M1.…”
Section: Discussionmentioning
confidence: 97%
“…EECs comprise approximately 1% of the intestinal epithelium and secrete hormones and peptides to recruit immune cells [34]. Distinctive staining of CHGA was observed for HROC43, HROC60, HROC159 T2 M4, and HROC239 T0 M1.…”
Section: Discussionmentioning
confidence: 97%
“…Peripheral 5-HT can circulate systemically via platelets and acted as a mitogen in injured organs. 79 , 80 In a murine model of liver injury, 5-HT promoted liver regeneration after partial hepatectomy, while mice lacking TPH1 could not fully regenerate their liver. 81 These findings suggested that EECs can undergo adaptive reprogramming during injury and provided insights for potential new regenerative therapeutics in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the closed type EECs are located basolaterally without direct contact with the lumen (Gribble & Reimann, 2016). Both types of EECs synthesize and store peptides or hormones in secretory granules and release them by exocytosis at the basolateral membrane upon mechanical, chemical or neural stimulation (Atanga et al, 2023). As open-type cells, L cells received both chemical and mechanical signals from the luminal contents, and neural signals from the nerves (Furness et al, 2013).…”
Section: Introductionmentioning
confidence: 99%